Risk Management Effectiveness of Oil And Gas Pipeline Construction in Java Island - Indonesia - I Putu Artama Wiguna; Nadjadji Anwar; Amien Widodo; Nova Nevila Rodhi (Institut Teknologi Sepuluh Nopember, 2017)
One of the important oil and gas industry is oil and gas pipeline which serves to support the gas transmission and distribution process. The oil and gas pipeline routes are so long and cross through some areas that certainly raises the risk of adversely affecting the environment, especially for the pipeline located in a densely populated area, where at certain conditions, the pipe can leak and may cause the explosion. Many researches have been conducted concerning on the project pipeline risks which concluded that the oil and gas pipeline project has very complex risks. In addition, the oil and gas project may cause a potential disaster. Currently oil and gas companies have been implementing risk management to minimize the negative impacts, but the negative impacts are still occurred. This is due to ineffective risk management implementation. This study aims to analyze the effectiveness of risk management system for oil and gas pipeline project in Java Island. Based on a deep study literature review, it shows that the effectiveness of risk management can be achieved by taking account into environmental, social and economic factors that are the pillars of sustainable development system. The potential disaster was also to be considered as an addition factor. Therefore, four identified factors were analyzed using Analytical Hierarchy Process (AHP) method. Data were obtained using questionnaire which were distributed to oil and gas project team. It is found that the most factors to be considered was social aspect (40%) and the other factors contributed 31% for disaster, 15% for economic, 14% for environment. Those factors should be taken account in the design stage as the most priority.